Clinical outcomes of limited open reduction and intramedullary nailing with steel cable cerclage in Seinsheimer III femoral subtrochanteric fractures - Cai, Hongru; He, XueYi; Zhang, Zhengchao; Chen, Pinhua; Wang, Ruoli; Fang, Qi; Xu, Zhixian; He, Wubing (Frontiers in medicine, 2025)
ObjectiveThis study aims to evaluate the clinical efficacy and safety of limited open reduction combined with intramedullary nailing and steel cable cerclage in treating Seinsheimer type III femoral subtrochanteric fractures. Surgical outcomes, fracture healing, pain relief, functional recovery, and complication rates were compared with intramedullary nailing alone.MethodsA retrospective cohort study was conducted on patients diagnosed with Seinsheimer III subtrochanteric fractures who underwent either intramedullary nailing alone (control group) or intramedullary nailing with steel cable cerclage (observation group). Surgical parameters (operation time, intraoperative blood loss, and hospital stay), bone healing indicators (callus formation, healing time, and swelling regression), postoperative pain (visual analog scale, VAS), hip function (Harris hip score at 1, 3, and 6 months), and complication rates (coxa vara, implant failure, infection, deep vein thrombosis) were compared. Statistical analyses were performed using SPSS 26.0, with a significance threshold of p < 0.05.ResultsThe observation group experienced significantly less intraoperative blood loss (p < 0.001) and shorter hospital stays (p < 0.001), with no difference in operation time (p = 0.996). Callus formation was more pronounced, and healing time and swelling regression were significantly faster in the observation group (all p < 0.001), indicating improved fracture stability and accelerated healing. VAS scores were lower postoperatively (p = 0.001), and functional recovery at 1 and 3 months was significantly better (p < 0.001), though similar outcomes were observed at 6 months (p = 0.126). The overall complication rate was lower in the observation group, especially for infections, though the difference was not statistically significant (p = 0.161).ConclusionLimited open reduction combined with intramedullary nailing and steel cable cerclage is a safe and effective approach for treating Seinsheimer III femoral subtrochanteric fractures. It provides faster bone healing, reduced intraoperative blood loss, improved early functional recovery, and does not increase complication risks. These findings support the clinical utility of steel cable cerclage as an adjunct fixation method, particularly for cases where closed reduction is challenging. Further prospective, large-scale studies are needed to confirm these results and refine surgical techniques for optimal patient outcomes.